FORMATION OF LOCAL STUDENT GROUPS TO INCREASE THE EFFICIENCY OF PRACTICAL TRAINING - Alexander A. Kel’Yin (Высшее образование в России)
The article describes the special method to form student groups for carrying out practical training. Each department form local student groups according to their achievements (rating) in the discipline. The best students are distributed into first group, and the weak ones! into the last group. Each group studies at its own comfortable speed and uses appropriate technologies. As a result - benefits for students, lecturers, and department administration.